2011
DOI: 10.1016/j.bcp.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid conjugates interact with organic anion transporters (OATs) and attenuate cytotoxicity of adefovir mediated by organic anion transporter 1 (OAT1/SLC22A6)

Abstract: . Flavonoid conjugates interact with organic anion transporters (OATs) and attenuate cytotoxicity of adefovir mediated by organic anion transporter 1 (OAT1/SLC22A6). Biochemical Pharmacology, Elsevier, 2011, 81 (7) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 45 publications
0
71
0
Order By: Relevance
“…It is already known that flavonoids and its conjugates (e.g., quercetin-3-O-glucuronide and quercetin-7-O-glucuronide) enter the cells via passive diffusion (Terao et al 2011;Wong et al 2012). In addition, several quercetin conjugates, e.g., quercetin-3′-O-sulfate, were also characterized as substrates of organic anion transporters [(OAT1, OAT3, and OAT4) (Wong et al 2011(Wong et al , 2012]. Quercetin was proposed to penetrate the plasma membrane to a high extent by passive diffusion (Terao et al 2011), but little is known about the involvement of other drug uptake transporters of the solute carrier (SLC) superfamily on the cellular accumulation of flavonoids aglycons such as quercetin and kaempferol.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that flavonoids and its conjugates (e.g., quercetin-3-O-glucuronide and quercetin-7-O-glucuronide) enter the cells via passive diffusion (Terao et al 2011;Wong et al 2012). In addition, several quercetin conjugates, e.g., quercetin-3′-O-sulfate, were also characterized as substrates of organic anion transporters [(OAT1, OAT3, and OAT4) (Wong et al 2011(Wong et al , 2012]. Quercetin was proposed to penetrate the plasma membrane to a high extent by passive diffusion (Terao et al 2011), but little is known about the involvement of other drug uptake transporters of the solute carrier (SLC) superfamily on the cellular accumulation of flavonoids aglycons such as quercetin and kaempferol.…”
Section: Introductionmentioning
confidence: 99%
“…These conjugated metabolites may contribute to inhibition as well. For example, Wong et al (2011) reported recently that several quercetin-conjugated metabolites, including quercetin-39-O-sulfate, quercetin-3-O-glucuronide, and quercetin-39-O-glucuronide, interact with OATs and attenuate the cytotoxicity of adefovir mediated by OAT1. For the flavonoids investigated in our study, the effects of conjugated metabolites are unknown due to the lack of metabolism by LLC-PK1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the inhibitory activities of these quercetin conjugates could be greater in the liver in vivo. The elimination half lives of quercetin metabolites in human studies were in the range of [10][11][12][13][14][15][16][17][18][19][20] hours. The relatively long half-lives of the quercetin conjugates imply that consumption of quercetin-rich foods can potentially inhibit hydroxycinnamic acid metabolism in vivo over a significant period of time (~1 day) [24].…”
Section: Discussionmentioning
confidence: 99%